2014
DOI: 10.1175/jcli-d-13-00268.1
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variations in ENSO Influences on Northwest Pacific–East Asian Early Summertime Climate Simulated in CMIP5 Models

Abstract: The present study investigates interdecadal modulations of the El Niño-Southern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 43 publications
(27 reference statements)
2
42
0
Order By: Relevance
“…16). A common bias of CMIP5 models is that the El Niño-induced IO warming and AAC terminate 1-2 months too early and do not persist through summer as in observations Hu et al, 2014). This bias of weak summer persistence might be due to a weak thermocline feedback of slow-propagating Rossby waves over the southwest IO-a mechanism that contributes to the persistence of the IPOC mode .…”
Section: Discussionmentioning
confidence: 94%
“…16). A common bias of CMIP5 models is that the El Niño-induced IO warming and AAC terminate 1-2 months too early and do not persist through summer as in observations Hu et al, 2014). This bias of weak summer persistence might be due to a weak thermocline feedback of slow-propagating Rossby waves over the southwest IO-a mechanism that contributes to the persistence of the IPOC mode .…”
Section: Discussionmentioning
confidence: 94%
“…This circulation causes SST warming withdraw to the west [ Figure 7; also refer to ) and (Huang et al, 2010)]. The westward extension of the anti-cyclonic atmospheric circulation over the NWP seems related to the ENSO structure that is displaced westward compared to observations in the equatorial region (Hu et al 2013).…”
Section: Atmospheric Forcing Over the Southeast Tiomentioning
confidence: 99%
“…Xie et al, 2009;Huang et al, 2010). The formation of the NWP anti-cyclonic circulation and its relationship to NIO warming in CMIP5 models are investigated in a companion study (Hu et al, 2013).…”
Section: Summary Summary Summary Summarymentioning
confidence: 99%
“…Cai et al (2015) showed that mean state change of the tropical Pacific will cause an increased frequency of extreme El Niño and La Niña events and an eastward shift of the ENSO rainfall teleconnections with a likely increased intensity. The CMIP5 models project a strengthening ENSO effect on the northwest Pacific and East Asia summer climate (Hu et al 2014).…”
Section: Introductionmentioning
confidence: 99%